The rebirth of Antisemitism in the 21st century
1 online resource.
Keywords: "The Rebirth of Antisemitism in the 21st Century is about the rise of anti-Zionism and Antisemitism in the first two decades of the 21st century, with a focus on the UK. It is written by the activist-intellectuals, both Jewish and not, who led the opposition to the campaign for an academic boycott of Israel. Their experiences convinced them that the boycott movement, and the anti-Zionism upon which it was based, was fuelled by, and in turn fuelled, Antisemitism. The book shows how the level of hostility towards Israel exceeded the hostility which is levelled against other states. And it shows how the quality of that hostility tended to resonate with Antisemitic tropes, images and emotions. Anti-Zionism positioned Israel as symbolic of everything that good people oppose, it made Palestinians into an abstract symbol of the oppressed, and it positioned most Jews as saboteurs of social 'progress'. The book shows how Antisemitism broke into mainstream politics and how it contaminated the Labour Party as it made a bid for Downing Street. This book will be of interest to scholars and students researching anti-Zionism, Antisemitism and the Labour Party in the UK"--